Best Ways of Vocabulary Memorisation in Foreign Language Learning: Cara Terbaik Menghafal Kosakata dalam Pembelajaran Bahasa Asing - Dushatova Shohsanam; Rahmonaliyeva Dildoraxon (Universitas Muhammadiyah Sidoarjo, 2022)
This scientific article presents a systematic and efficient method to facilitate the memorization of unfamiliar English words for language learners while promoting long-term retention. The study addresses key challenges faced by English language learners, including the correct interpretation of test questions and translation issues. The goals of the research encompass the development of an easy, fast, and effective vocabulary memorization technique. To achieve these goals, a comprehensive approach incorporating various strategies such as contextual learning, mnemonic devices, and spaced repetition was employed. Results demonstrate significant improvements in participants' vocabulary acquisition and retention, as evidenced by enhanced performance on test questions and enhanced accuracy in English translation tasks. The implications of this study suggest that educators and learners can benefit from the implemented approach to enhance vocabulary learning and retention in English language acquisition, ultimately fostering overall language proficiency. Highlights: Effective Vocabulary Memorization: This scientific article presents a comprehensive approach to aid English language learners in effectively memorizing unfamiliar words, ensuring long-term retention. Diverse Strategies for Vocabulary Acquisition: The study incorporates various strategies, including contextual learning, mnemonic devices, and spaced repetition, to facilitate vocabulary acquisition and enhance language proficiency. Improved Test Performance and Translation Accuracy: The implemented approach resulted in notable improvements in test question interpretation and English translation tasks, highlighting the practical implications for language learners and educators. Keywords: English language learners, vocabulary memorization, effective retention, comprehensive approach, language acquisition.